Copagamento dos usuários no Programa Farmácia Popular do Brasil: Um estudo exploratório da rede conveniada - Aléssio Tony Cavalcanti de Almeida; Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This text has as main objective to calculate the users' co-payment values in the Brazilian Farmácia Popular program (PFPB), as well as to explore potential factors associated with the co-payment rate in the program. The study is based on a rich set of data relating to product sales by accredited private pharmacies from March 2006 to September 2019, with about two billion program administrative records. The average of co-payment value was calculated from the difference between the average sales price and the value subsidized by the Ministry of Health (MOH) per package, stratifying this value by indication of the product, type of drug (generic, similar and reference) and federative unit. The results show that the average co-payment rate (TCP) of the user in the PFPB was 37.6% per product packaging, with an upward trend from 2016. From 2009 to 2015, it was found that TCP was prone to reduction for the co-payment product group, which is composed of products that have always been co-paid since the beginning of the program. In addition, this propensity was driven by the average TCP of the drugs indicated for dyslipidemia (which accounts for two thirds of the co-payment group authorizations). In the period analyzed, similar drugs were being replaced by generic drugs. A specific analysis for the drug simvastatin, used to treat dyslipidemia, showed a low concentration of manufacturers in the market and a significant reduction in their sales prices, which helps to understand the dynamics of TCP. Regionally, North and Northeast states tended to have lower co-payment rates over the period. In 2019, for example, TCP for the North and Northeast beneficiaries was 9.0 and 7.5 percentage points lower than the Southeast region, respectively. The results of this work demonstrate that the subsidy given by the MOH for drugs in PFPB is a relevant factor in determining access to medicines in the program. Reductions in this subsidy during the period analyzed resulted in increased co-payment and, consequently, in TCP, with a decrease in program authorizations, number of beneficiaries and pharmacy prescriptions. Subsidy increases led to increased demand. However, the magnitude of the subsidy is not the only factor determining co-payment and TCP by users. The selling price of the same drug may be affected by the taxes in each federative unit and by the degree of competition among pharmaceutical establishments and the products on the market. Finally, the evidence produced in this study fills a gap in the literature on PFPB by sizing the effective co-payment rate of users in the program, making more evident the influence of pharmacy prices and government subsidized values on products access dynamics by the population.
Keywords: I18; H24; 330; access to essential medicines and health technologies; pharmaceutical preparations; public policy; pharmaceutical services; co-payment; Brazil